2020
DOI: 10.1302/0301-620x.102b9.bjj-2020-0096.r1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing tibial migration of the ATTUNE cemented cruciate-retaining knee prosthesis with the PFC-sigma design

Abstract: Aims The primary objective of this study was to compare migration of the cemented ATTUNE fixed bearing cruciate retaining tibial component with the cemented Press-Fit Condylar (PFC)-sigma fixed bearing cruciate retaining tibial component. The secondary objectives included comparing clinical and radiological outcomes and Patient Reported Outcome Measures (PROMs). Methods A single blinded randomized, non-inferiority study was conducted including 74 patients. Radiostereometry examinations were made after weight b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 38 publications
2
43
1
Order By: Relevance
“…Although our study is not powered to evaluate clinical results, the scores on the FJS 50 and KOOS 30 , 51 are consistent with other TKAs. The polyethylene wear over two years was not clinically relevant (p = 0.116, Wilcoxon signed-rank test).…”
Section: Discussionsupporting
confidence: 68%
“…Although our study is not powered to evaluate clinical results, the scores on the FJS 50 and KOOS 30 , 51 are consistent with other TKAs. The polyethylene wear over two years was not clinically relevant (p = 0.116, Wilcoxon signed-rank test).…”
Section: Discussionsupporting
confidence: 68%
“…A key study using model-based RSA compared migration, and clinical and patient-reported outcomes, between the ATTUNE design and PFC-sigma design. 21 The authors reported comparable tibial component migration at two years, but with more radiolucent lines observed at the implant-cement interface with the ATTUNE design, reinforcing that additional radiological parameters should be considered. Moreover, we need to be attentive to the failure mode, as there are exceptions in the behaviour of each implant.…”
mentioning
confidence: 72%
“…27 The role of RSA has once again been vital in assessing micromotion and adjudicating the safety of these designs. 4,21,28 Other potential applications of RSA include in vivo linear and volumetric wear using model-based radiostereometric analysis. [29][30][31][32][33] Gascoyne et al 30 used modelbased RSA to evaluate linear and volumetric polyethylene (PE) wear in 101 TKA patients.…”
mentioning
confidence: 99%
“…The findings of Kaptein et al 8 also agreed with those of Hoskins et al 30 They undertook a randomized controlled trial comparing the migration of the tibial component of 38 Attune cemented CR TKAs with 36 PFC-sigma TKAs. 8 At two years postoperatively, radiolucencies were seen between the Attune medial baseplate and the cement in 14 TKAs (42%) compared with three in Sigma PFC TKAs (9%). Staats et al 9 reviewed 529 primary cemented Attune and PFC Sigma TKAs which were implanted between 2014 and 2017 and also found a significantly higher incidence of radiolucent lines in the Attune group compared with the PFC group at 12 months postoperatively (35.1% vs 7.5%; p < 0.001).…”
Section: Discussionmentioning
confidence: 95%
“…[5][6][7] Others have reported an increased incidence of periprosthetic radiolucencies at early follow-up in patients treated the same designs of implant. 8,9 A number of reasons have been proposed. For the Attune (DePuy, USA), these include an increased constraint of the tibial PE, the absence of cement pockets on the tibial tray, changes in the roughness of the backside surface of the tibial tray, and stress-shielding secondary to the use of a thicker cobalt-chromium (CoCr) tray.…”
Section: Introductionmentioning
confidence: 99%